Description of Barbus teugelsi sp. nov. (Cypriniformes: Cyprinidae) from the Little Scarcies basin in Guinea, Africa - Bamba, Mamadou; Vreven, Emmanuel J.; Snoeks, Jos (Zootaxa, 2011)
Barbus teugelsi, a new African cyprinid, is described from the Mongo River at Marela (Guinea). It is morphologically similar to the syntopically occurring ‘B.’ bigornei Lévêque et al. 1988, with which it has been confounded in the past. However, the scale meristics of the new species differ from those of ‘B.’ bigornei, but are similar in all but one to those of ‘B.’ ablabes (Bleeker 1863) and ‘B.’ parablabes Daget 1957. Barbus teugelsi sp. nov. is clearly distinguished from both these species by the following unique combination of characters: a lower total number of gill rakers on the first gill arch (3–6); the presence of long barbels, with the anterior barbels reaching the vertical passing through the middle of the eye and the posterior barbels extending beyond the vertical passing through the posterior edge of the eye and reaching the pre-operculum. In addition, the cephalic sensory canals are highly reduced or even absent. Furthermore, small differences between the new species and the other three species were found for several measurements. A short discussion on the taxonomic value of some diagnostic characters in small barbs is included.